Policies for REgional COoperation in the field of Lifelong Learning - Federighi, Paolo (Proceedings e report, 2010)
This document constitutes the Policy Paper of the Precoll project-Policies for Regional Cooperation in Lifelong Learning, led by the Università degli Studi di Firenze-Dipartimento di Scienze dell'Educazione e dei Processi Culturali e Formativi/University of Florence-Department of Educational Sciences and Cultural and Training Processes (Agreement nr 2008-11294), in partnership with Generalitat de Catalunya, Junta de Andalucía, Regione Toscana, Welsh Assembly Government, Jämtland County Council, NIACE Dysgu Cymru-National Institute of Adult Continuing Education, Provincia di Livorno Sviluppo Srl, subcontractor Melius Srl (www.mutual-learning.eu). This document has been endorsed by the Earlall General Assembly held in Brussels on 16th February 2010. Moreover Cedefop has been supporting the quality of the work thanks to the regular advice and suggestions delivered by Steven Bainbridge.